Experience Design Modelling of the Relationship between Patient Recovery and Hospital Design in the Kingdom of Saudi Arabia - Al Ghamdi, Abdullah Mohammed A (Curtin University, 2021)
This study investigates the relationship between hospital design, development and operational stages and patient recovery in public hospitals in the Kingdom of Saudi Arabia. It examines environmental design issues in relation to stakeholders’ satisfaction by analysing events that support patient's healing and recovery as well as the effectiveness of care services. To achieve these, the study focuses on patient health recovery causations [that is, factors, requirements, needs and causes that influence patients’ health] and the roleplayed by the current design process in Saudi’s public hospitals.